Performance of Sorghum (Sorghum bicolor L. Moench) as an energy crop for biogas production - Mahmood, Athar; Justus Liebig University Giessen (My University, 2011)
Sorghum (Sorghum bicolor (L.) Moench) belonging to the Tribe Andropogonae of the family Poaceae is cultivated in tropical and subtropical regions and variously used for the production of animal feed as well as for energy and syrup. Presently sorghum is a new crop in Germany and still not well adapted to the local climate. So there is a dire need to produce adapted cultivars and to optimize husbandry practices of sorghum for its cultivation in Germany. One of the most important demands on sorghum cultivation is the establishment of plant stand. For that reason field experiments were conducted to clarify the effect of different sowing times, row spacing and plant densities on dry matter production, chemical composition, and biogas production of sorghum.Two field experiments were carried out at three experimental stations in Giessen, Gross-Gerau and Rauischholzhausen in 2008 and 2009. First experiment was conducted to study the impact of different plant densities (16, 24 and 32 plants m-2), sowing times (mid of May, end of May and first week of June) and cultivars (Goliath and Bovital). On the other hand the second experiment was conducted to clarify the effect of different row spacing (75 cm, 37.5 cm and 75 cm double row apart with strip rows of 10-15 cm) and cultivars (Goliath, Bovital, Aron, Rona 1 and Akklimat) on biomass yield, chemical composition and methane productivity of Sorghum bicolor. The field trials were designed in RCBD under split plot arrangement with four replications and statistically analyzed by using PIAF software.It was observed that higher plant density and wider row spacing decreased the number of tillers per plant. On the other hand, higher plant density and narrow row spacing led to higher leaf area index (LAI). The biomass yield of sorghum varied from minimal 5.0 to maximal 17.0 t DM/ha in present trials. In most cases dry matter yield was not significantly affected by plant density as well as by row spacing evaluated in present trials. However in one experiment, narrow row spacing (37.5 cm and 75 cm double row apart with strip rows of 10-15 cm) led to significantly higher dry matter yield compared with wider row spacing of 75 cm. In twelve from total eighteen sowing times, different plant densities led to comparable averages of dry matter yield. However in six sowing times, higher plant densities (24 and 32 plants m-2) exhibited significantly greater dry matter yield than lower plant density (16 plants m-2). Under the specific experimental conditions, it was found that sorghum can be cultivated by delayed sowing until mid of June without compromising the dry matter yield. Among five tested cultivars, Goliath was characterized by consistently higher dry matter yield than other tested cultivars in all experiments conducted at different experimental stations. Despite of higher number of tillers per plant, cv. Akklimat showed lowest LAI while comparable values were observed for cv. Goliath, Bovital, Aron and Rona 1. Row spacing and plant density had no clear impact on most quality parameters (protein, neutral detergent fiber, acid detergent fiber and lignin concentration) of sorghum plants. However significant interactions of cultivar x plant density in 1st and 2nd sowing time (Giessen 2008) and 1st sowing (Gross-Gerau 2009) were observed. Cv. Goliath showed a reduction in protein concentration at lower plant density while similar averages were attained for cv. Bovital. The neutral detergent fiber (NDF) concentrations varied from 50 to 56% of DM. In some treatments, significant interactions of cultivar x plant density were found regarding NDF and ADF concentration. Cultivars clearly influenced the chemical composition of sorghum. Protein concentrations of tested cultivars ranged from 6 to 9%. Higher protein concentrations were achieved by Sorghum sudanense like cv. Akklimat and cv. Bovital than Sorghum bicolor species tested in present experiments. Contrary to that Sorghum bicolor (cv. Aron and cv. Rona 1) accumulated markedly higher sugar concentration compared with Sorghum sudanense species such as cv. Bovital and cv. Akklimat. Lowest acid detergent fiber, neutral detergent fiber and ash concentrations were exhibited by cv. Rona 1 followed by cv. Aron among cultivars. In present study, specific methane yield of sorghum ranged from 280 to 387 nL kg-1 of volatile solid. Cv. Rona 1 reached higher specific methane yield (Norm litter CH4 per kg of volatile solids) than other tested cultivars. Although cv. Rona 1 produced higher specific methane yield per kg volatile solid but it was overcompensated by cv. Goliath due to higher dry matter yield ha-1. Thus the cv. Goliath may have advantage over the cultivars of this study, due to its higher dry matter potential for the maximization of methane yield ha-1.

Sorghum (Sorghum bicolor (L.) Moench, Tribus Antropogonae, Familie Poaceae) ist eine in den subtropischen und tropischen Regionen angebaute Kulturpflanze, die vor allem zur Produktion von Tierfutter, Bioenergie und Sirup genutzt wird. In Deutschland ist Sorghum gegenwärtig eine relativ neue Kulturpflanze, die noch nicht ausreichend an die hiesigen klimatischen Bedingungen adaptiert ist. Aus diesem Grund ist es erforderlich, neue angepasste Sorten zu schaffen und die Methoden für einen Anbau von Sorghum in Deutschland zu optimieren. Eine wichtige Voraussetzung für die erfolgreiche Kultivierung von Sorghum ist die Etablierung des Pflanzenbestandes. Aus diesem Grund wurden Feldversuche durchgeführt, in denen der Einfluss verschiedener Saatzeiten, Reihenweiten und Pflanzendichten auf die Trockenmasseproduktion, die chemische Zusammensetzung und die Biogasausbeute geklärt werden sollte. In den Jahren 2008 und 2009 wurden zwei Feldversuche an insgesamt drei Standorten in Gießen, Groß-Gerau und Rauischholzhausen durchgeführt. Im ersten Versuch wurden unterschiedliche Bestandesdichten (16, 24 und 32 Pflanzen/m2) und verschiedene Saatzeiten (Mitte Mai, Ende Mai, erste Juniwoche) in Kombination mit zwei Sorten ( Goliath und Bovital ) geprüft. Im zweiten Versuch wurde der Einfluss unterschiedlicher Reihenentfernungen (75 cm, 37,5 cm und 75 cm Doppelreihen mit Streifenreihen von 10 - 15 cm) in Kombination mit fünf Sorten (Goliath, Bovital, Aron, Rona 1 und Akklimat) auf den Biomasseertrag, die chemische Zusammensetzung und die Methanausbeute untersucht. Die Feldversuche wurden in Form von zweifaktoriellen Spaltanlagen mit vier Wiederholungen durchgeführt und mit Hilfe des PIAF-Programms statistisch ausgewertet.Aus den Ergebnissen ist zu erkennen, dass höhere Pflanzendichten und größere Reihenabstände zu einer geringeren Triebzahl pro Pflanze und gleichzeitig zu einem höheren Blattflächenindex führten. Der Biomasseertrag von Sorghum variierte in den durchgeführten Versuchen von 5 bis 17 t TM/ha. In den meisten Versuchen hatten die Pflanzendichten und Reihenabstände keinen signifikanten Einfluss auf die Biomasseerträge von Sorghum. In einem Versuch dagegen führten engere Reihenweiten von 37,5 cm und Doppelreihen (Streifen von 10 - 15 cm) zu signifikant höheren Trockenmasseerträgen im Vergleich mit großen Reihenweiten von 75 cm. In zwölf von insgesamt achtzehn durchgeführten Saatzeiten hatte die Veränderung der Pflanzendichte keinen Einfluss auf den TM-Ertrag. In sechs weiteren Saatzeiten bewirkten höhere Pflanzendichten (32 und 24 Pflanzen/m2) dagegen signifikant höhere Trockenmasseerträge im Vergleich mit geringeren Pflanzendichten von 16 Pflanzen/m2. Unter den spezifischen Versuchsbedingungen zeigte sich, dass die Aussaat von Sorghum bis Mitte Juni zu keiner Beeinträchtigung der Trockenmasseerträge führte. Unter den fünf getesteten Sorten erreichte die Sorte Goliath an allen Versuchsstandorten die höchsten Trockenmasseerträge. Trotz höherer Triebzahl/Pflanze wurden bei der Sorte Akklimat die geringsten LAI-Werte gemessen, während die LAI-Werte bei den übrigen getesteten Sorten vergleichbar waren.Die Prüffaktoren Reihenweite und Pflanzendichte hatten keinen gesicherten Einfluss auf die meisten Qualitätsparameter (Gehalte an Eiweiß, NDF, ADF und Lignin). Dagegen zeigten sich signifikante Interaktionen zwischen Sorte und Pflanzendichte in der 1. und 2. Saatzeit in Gießen 2008 und in der 1. Saatzeit in Groß-Gerau 2009. Es wurde festgestellt, dass die Sorte Goliath im Gegensatz zu den Vergleichssorten auf die Verringerung der Pflanzendichte mit einer Reduktion der Eiweißkonzentration reagierte. Die NDF-Werte variierten von 50 bis 56% der TM. In einigen Versuchen wurden hinsichtlich der NDF- und ADF-Konzentration signifikante Interaktionen zwischen den Prüffaktoren Sorte und Pflanzendichte beobachtet. Die chemische Zusammensetzung der Biomasse von Sorghum wurde deutlich durch die jeweilige Sorte bestimmt. Die Proteinkonzentration der geprüften Sorten variierte von 6 bis 9%. Sorten der Spezies Sorghum sudanense (cv. Akklimat und cv. Bovital) wiesen höhere Proteinkonzentrationen auf als Sorten von Sorghum bicolor. Im Gegensatz dazu lagen die Zuckerkonzentrationen bei den Sorghum bicolor-Sorten Rona 1 bzw. Aron deutlich höher als bei Sorghum sudanense. Die geringsten ADF-, NDF- und Aschegehalte wies die Sorte Rona 1 auf, gefolgt von der Sorte Aron . Die spezifischen Methanerträge variierten in den durchgeführten Versuchen von 280 bis 387 nL kg-1. Die Sorte Rona 1 erreichte die höchsten spezifischen Methanerträge (Normliter CH4/kg oTS) im Vergleich zu die übrigen Sorten. Dennoch erreichte unter dem Aspekt des Methanertrags/Flächeneinheit die Sorte Goliath die höchsten Erträge, da sie die höchsten Trockenmasseerträge bei gleichzeitig ausreichenden Methangehalten aufwies.
Der Nutzeffekt von Sorghum als Energiegetreide für die Biogasproduktion
Keywords: ddc:630